2009
DOI: 10.2478/s11686-009-0017-3
|View full text |Cite
|
Sign up to set email alerts
|

Parasite fauna of the mediterranean grenadier Coryphaenoides mediterraneus (Giglioli, 1893) from the Mid-Atlantic Ridge (MAR)

Abstract: A total of 38 Coryphaenoides mediterraneus from the Charlie-Gibbs Fracture Zone (CGFZ), a part of the Mid-Atlantic Ridge (MAR), was studied for parasites and feeding ecology. Sixteen different parasite species were found, most of them belonging to the Digenea (6 species) and Nematoda (6). Twelve new host and 11 new locality records were established, and 8 deep-sea generalists and 5 deep-sea specialists were found. Twelve adult and 3 larval parasites occurred, with Allopodocotyle margolisi (Digenea), Tetraphyll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…There are several species described in the Gonocerca genus, namely G. phycidis Manter [1]; G. kobayashi Layman [22]; G. crassa Manter [8]; G. macroformis Wolfgang and Myers [9]; G. oregonensis McCauley et al [23]; G. lobata Byrd [24]; G. trematomus Byrd [24]; G. japonica Toman [25]; and G. caetorinchi Machida and Kuramochi [26]. Morphological and morphometric comparison revealed that in our study, the Gonocerca species is closely related to G. phycidis previously described by Zdzitowiecki [27] from Pseudochaenichthys georgianus in South Georgia; Suriano and Sutton [28] from Macroronus magellanicus in San Matías Gulf, Argentina; Kellermanns et al [29] from Macrourus berglax in Admiralty Bay, Indian Ocean; and Guagliardo et al [21] from Seriolella porosa in San Matías Gulf, Argentina; because of their remarkable similarities in the measurements of the different body parts. G. phycidis has a wide host range, infecting members of different fish families.…”
Section: Discussionsupporting
confidence: 75%
“…There are several species described in the Gonocerca genus, namely G. phycidis Manter [1]; G. kobayashi Layman [22]; G. crassa Manter [8]; G. macroformis Wolfgang and Myers [9]; G. oregonensis McCauley et al [23]; G. lobata Byrd [24]; G. trematomus Byrd [24]; G. japonica Toman [25]; and G. caetorinchi Machida and Kuramochi [26]. Morphological and morphometric comparison revealed that in our study, the Gonocerca species is closely related to G. phycidis previously described by Zdzitowiecki [27] from Pseudochaenichthys georgianus in South Georgia; Suriano and Sutton [28] from Macroronus magellanicus in San Matías Gulf, Argentina; Kellermanns et al [29] from Macrourus berglax in Admiralty Bay, Indian Ocean; and Guagliardo et al [21] from Seriolella porosa in San Matías Gulf, Argentina; because of their remarkable similarities in the measurements of the different body parts. G. phycidis has a wide host range, infecting members of different fish families.…”
Section: Discussionsupporting
confidence: 75%
“…Additional studies in the North Atlantic have been conducted by Wilhelm et al, (2008); Kellermanns, et al, (2009) and Klimpel et al, (2006;2010), among others. Parasite assemblages of deep-sea fishes collected from the Antarctic Ocean have been studied by Walter et al (2002), whereas Brickle et al (2005); Dallarés et al (2014); Mateu et al (2015) and Constenla et al (2015) analyzed the parasite fauna of Mediterranean deep-sea fishes.…”
Section: Introductionmentioning
confidence: 96%
“…The position of Allopodocotyle margolisi in the other major opecoelid clade, along with other deep-sea fish parasites, indicates that some convergence appears to have occurred. Allopodocotyle margolisi is the only deep-sea member of the nominal genus and is genuinely deep-sea, having been found at depth between 1 700-3 500 m off the west coast of Scotland and at the Mid-Atlantic Ridge (Gibson 1995, Kellermanns et al 2009). …”
Section: Clade Bmentioning
confidence: 99%